2022
DOI: 10.3389/fimmu.2022.940867
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Function of Kupffer Cells in Liver Injury

Abstract: Kupffer cells (KCs) are key regulators of liver immunity composing the principal part of hepatic macrophages even body tissue macrophages. They reside in liver sinusoids towards portal vein. The micro-environment shapes KCs unique immunosuppressive features and functions. KCs express specific surface markers that distinguish from other liver macrophages. By engulfing gut-derived foreign products and apoptotic cells without triggering excessive inflammation, KCs maintain homeostasis of liver and body. Heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 113 publications
0
28
0
1
Order By: Relevance
“…Although certain extrahepatic sites, such as adipose tissue, have evolved as major sources of inflammatory mediators in obesity-related disorders, evidence is accumulating that intrahepatic inflammation might also be critically involved in the pathogenesis of NAFLD ( 39 , 40 ). Although multiple cell populations in the liver contribute to various inflammatory pathways, hepatic macrophages are considered key contributors to the process of metabolic inflammation that underlies the development of NAFLD ( 41 ). The functional heterogeneity of monocyte-derived macrophages was initially typified by their polarization into M1 and M2 phenotypes, which were thought to represent two ends of a spectrum in which M1 macrophages are proinflammatory and M2 macrophages are regenerative ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although certain extrahepatic sites, such as adipose tissue, have evolved as major sources of inflammatory mediators in obesity-related disorders, evidence is accumulating that intrahepatic inflammation might also be critically involved in the pathogenesis of NAFLD ( 39 , 40 ). Although multiple cell populations in the liver contribute to various inflammatory pathways, hepatic macrophages are considered key contributors to the process of metabolic inflammation that underlies the development of NAFLD ( 41 ). The functional heterogeneity of monocyte-derived macrophages was initially typified by their polarization into M1 and M2 phenotypes, which were thought to represent two ends of a spectrum in which M1 macrophages are proinflammatory and M2 macrophages are regenerative ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that non-parenchymal liver cells have important function in the tolerance induction following LT ( Knechtle and Kwun., 2009 ). Kupffer cells proved to have a dual performance in the pathological changes that occur after LT, Th1 cells correlated with rejection and Th2 predominance favoured graft acceptance and immunological tolerance ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mature KCs share a series of common macrophage surface markers, such as CD11 and F4/80, whereas KCs in mice express the unique marker, C-type lectin domain family 4 member F (CLEC4F) ( Krenkel and Tacke, 2017 ; Li W. et al, 2022 ). These KCs usually inhabit liver sinusoids, where they continuously engage with and process senescent cells and various gut-derived particles.…”
Section: The Origin and Characteristics Of Hepatic Macrophagesmentioning
confidence: 99%
“…Two main categories of macrophages are present in the liver: liver-resident Kupffer cells (KCs) and circulating monocyte-derived macrophages (MoMφs) ( Varol et al, 2015 ; Dou et al, 2019 ). In general, KCs are responsible for sensing and processing biochemical signals, such as pathogen components, cell fragments, and endo/exogenous metabolites ( Diehl et al, 2020 ; Li W. et al, 2022 ). They can trigger primary inflammation and secrete chemokines to recruit MoMφs for further inflammatory responses ( Wen et al, 2021 ; Zhou J. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation